The Conflict Resolution Toolbox, 2nd Edition - Furlong, Gary; Moore, Christopher (Wiley, 2020)
PRAISE FOR THE CONFLICT RESOLUTION TOOLBOX SECOND EDITION "I have been using and recommending The Conflict Resolution Toolbox since its first edition. It is rare to find a resource with such practical tools in a field that is so concrete, but often struggles to bridge theory and practice. In this increasingly complex world, it is vital to have models to resort to when we reach impasse in conflict. I recommend The Conflict Resolution Toolbox to anyone engaged in resolving conflicts in any discipline." -Martha E. Simmons, JD, LLM, PHD, Academic Director, Winkler Institute of Dispute Resolution and Director, Mediation Clinic and Intensive Program, Toronto, Canada "We all know one thing about conflict: It is messy! Furlong's models offer mediators, facilitators, lawyers, psychotherapists and others 'a leg up' in more swiftly figuring out what is going on and what is needed. Furlong does not offer up a single 'truth', style or theory, so much as a collection of effective tools that professionals, groups and families can use to better understand what they are experiencing and how they can approach achieving better results. Highly recommended!" -James C. Melamed, JD, CEO, Mediate.com "Gary Furlong has done it again! A long-time leader in the conflict resolution field, Gary has added two new 'power tools' to what was already the essential conflict resolution toolkit. His new chapters in this Second Edition deal with 'The Law of Reciprocity' and 'Loss Aversion Bias'. I am proud and thankful to add this book to my already growing conflict resolution bookcase, knowing that this is a volume I will go to again and again. I highly recommend it for anyone in the field." -Rick Weiler, Mediator, Arbitrator, Weiler ADR Inc., Ottawa, Canada "Gary Furlong uniquely provides invaluable, practical tools that help in understanding, preventing, and resolving conflict. This is a must-have reference book for anyone who cares about mitigating the role destructive conflict plays in our professional and personal lives and finding strategic benefit in tools that work. Gary has created a book that is both aspirational and practical. It's so challenging to create simple-to-use tools supported by complex concepts and Gary does this better than anyone." -Joshua A. Gordon, JD, MA, Arbitrator for the Court of Arbitration of Sport, Senior Practitioner at the Sports Conflict Institute, and Woodard Family Foundation Fellow Senior Instructor of Sports Business at the University o...